Specialist nursing case management support for carers of people with dementia: A qualitative study comparing experiences of carers with and without Admiral Nursing. (24th May 2021) - Gridley, Kate; Parker, Gillian
Abstract: Carers of people with dementia can experience reduced health and well‐being, but little is known about how best to support them. There is some evidence to suggest that case management may improve outcomes for carers but less evidence about the features of case management services that can effectively support carers of people with dementia. Admiral Nursing operates a case management approach staffed by specialist nurses and is the only service of its kind in the United Kingdom dedicated to helping people with dementia and their carers. This paper reports qualitative findings from a mixed methods study of Admiral Nursing. For the qualitative strand of the project, data were collected in focus groups and in‐depth interviews with carers of people with dementia ( n  = 35) and analysed thematically using the framework approach. The aim of this analysis was to understand differences between the experiences of the carers in our sample with and without Admiral Nursing, applying Freeman's model of continuity of care (Freeman et al., Continuity of care, 2000). Participants who had received Admiral Nursing were recruited from two geographical locations and carers without experience of this service were recruited from two different areas. We found that carers in our sample felt 'supported' in circumstances where they received an ongoing service from an Admiral Nurse or other professional with expertise in dementia who was able to develop a meaningful relationship with them over time. We conclude that ongoing support, expertise in dementia and a meaningful relationship are key features of relationship continuity common in carers' reports of feeling supported. Specialist nurses are well placed to provide this continuity.